2011
DOI: 10.1159/000333368
|View full text |Cite
|
Sign up to set email alerts
|

Brain Alterations and Mini-Mental State Examination in Patients with Progressive Supranuclear Palsy: Voxel-Based Investigations Using 18F-Fluorodeoxyglucose Positron Emission Tomography and Magnetic Resonance Imaging

Abstract: Background/Aims: The aim of this study was to compare differences in morphological and functional changes in brain regions in individual patients with progressive supranuclear palsy (PSP) and correlate their Mini-Mental State Examination (MMSE) score with anatomy and function using magnetic resonance imaging (MRI) and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET). Methods: Sixteen PSP patients and 20 age-matched healthy volunteers underwent FDG-PET and 3-dimensional MRI. Gray matter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…We identified 32 studies in the database searches (Figure 1 ) including nine PSP-HC articles (Brenneis et al, 2004 ; Cordato et al, 2005 ; Boxer et al, 2006 ; Padovani et al, 2006 ; Agosta et al, 2010 ; Lehericy et al, 2010 ; Takahashi et al, 2011 ; Ghosh et al, 2012 ; Giordano et al, 2013 ). One hundred and fourty-five PSP patients and 217 HC were included in this study and a total of 104 foci with reduced GMV were reported.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 32 studies in the database searches (Figure 1 ) including nine PSP-HC articles (Brenneis et al, 2004 ; Cordato et al, 2005 ; Boxer et al, 2006 ; Padovani et al, 2006 ; Agosta et al, 2010 ; Lehericy et al, 2010 ; Takahashi et al, 2011 ; Ghosh et al, 2012 ; Giordano et al, 2013 ). One hundred and fourty-five PSP patients and 217 HC were included in this study and a total of 104 foci with reduced GMV were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of [ 18 F]-fluorodeoxyglucose PET (FDG-PET) have shown hypometabolism in the midbrain, basal ganglia, thalamus, and frontal lobes in PSP-RS, [132][133][134][135][136][137][138][139][140][141][142][143][144][145] with frontal involvement particularly targeting premotor, precentral, and prefrontal regions 134 and anterior cingulate 146 (Fig. 2A).…”
Section: Pet/spect [ 18 F]fdg-petmentioning
confidence: 99%
“…Moreover, 33 % of asymptomatic relatives showed cortical and subcortical hypometabolism suggesting the presence of subclinical PSP [ 48 ]. [ 18 F]FDG PET was used to investigate neural correlates of PSP symptoms [ 49 52 ]. A PET study investigated the brain network relevant to postural imbalance and falls in a cohort of 16 PSP patients [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Smooth pursuit eye movement was correlated with hypometabolism in the inferior parietal and temporal regions and frontal eye field [ 52 ]. Reduced glucose metabolism in the frontal cortex was associated with worse Mini Mental Status Examination (MMSE) scores in 16 PSP patients the presence of frontal lobe dysfunction in PSP [ 49 ]. Frontal brain regions and in specific cingulate gyrus hypometabolism is also a feature of Frontotemporal Dementia [ 53 57 ].…”
Section: Resultsmentioning
confidence: 99%